INTRODUKSI HIJAUAN UNGGUL RUMPUT ODOT (Pennisetum purpureum cv. Mott) SEBAGAI SUMBER PAKAN UNTUK PETERNAK SAPI DESA SIDANGKASIH - Widhi Kurniawan; Ali Bain; La Ode Nafiu; Nur Santy Asminaya; Hamdan Has; Asma Bio Kimestri (Universitas Halu Oleo, 2021)
Farmers in rural areas generally take advantage of the available feed sources around them. Their feed is fulfilled by utilizing agricultural by-products and natural forage available. Sindangkasih Village is well known as a transmigrant community from Java and Bali. Most of the people of Sindangkasih work as farmers and ranchers who are not familiar with high quality forages and how to cultivate them for animal feed. This program is to introduce the community in Sindangkasih Village to the potential of odot grass that can be cultivated as animal feed. So, the location is expected to be an area that has a variety of high-quality forage feeds for livestock, one of which is odot grass. The introduction of odot grass as a high-quality forage program is carried out as one of the leading service programs integrated with KKN thematic Program in 2021. The method used in implementing this program is to carry out counselling, direct practice and assistance in making odot grass nursery garden demo plots. The participants understanding the principles of odot grass cultivation easily and are able to adopt good cultivation techniques.